Enhanced Cloud Service Broker Selection Policy Based On Differential Evolution Algorithm - Sanjalawe, Yousef Khader Khattar (2020)
Cloud computing (CC) is speedily an emerging technology in the Information Technology sector and is becoming a pivotal research area. CC permits cloud service providers to provide different types of cloud services to different users. Cloud users are willing to meet their requests demands at the lowest cost and minimum processing time and response time, which is highly dependent on the data center (DC) that is responsible for executing the requests. The selection of a DC in the CC environment is the responsibility of the Cloud Service Broker (CSB) that operates in accordance with a built-in routing policy. Improper DC selection might cause a bottleneck and congestion in the service brokerage architecture, resulting in resource leakage in termsof time and cost.